Buckling analysis of an inflated arch including wrinkling based on Pseudo Curved Beam model. (October 2018) - Xue, Z.M.; Wang, C.G.; Kang, J.T.; Tan, H.F.
Abstract: A Pseudo Curved Beam (PCB) model is proposed to analyze the buckling behaviors of inflated arch. The wrinkling (local buckling) effect is considered in the PCB model by modifying the cross-sectional area and sectional moment of inertia in the stiffness matrix. The wrinkling angle, wrinkling and failure load are then predicted based on the proposed PCB model. The bending experiment and numerical simulation of a quarter-circle inflated arch are performed to verify the validation of the PCB model. The effects of load conditions, constraint conditions, structural geometric parameters, inflation pressure and material properties on the buckling characteristics of inflated arch are parametrically studied in the end. The method and results provide good references for the load-carrying design of inflated structures. Graphical abstract: Highlights: A PCB model is proposed to analyze the buckling behavior of inflated arch structure. The wrinkling effect is considered by modifying the stiffness matrix. The wrinkles decrease 66% failure load of the inflated arch. The buckling load is sensitive to inflation pressure, load distribution and slenderness ratio. The change of buckling load mainly caused by the transformation of buckling mode.